Modularized PCA pump design for an ICE-informed medical device coordination framework - Luan, Shiwei (Kansas State University, 2015)
Medical device interoperability and re-configurability continue to be important areas of research toward the realization of verifiable medical systems that can be rapidly assembled to meet the needs of specific patients. This thesis addresses the modularized design of a patient-controlled analgesia (PCA) pump to be used within the context of the Medical Device Coordination Framework (MDCF), an open source framework under development by Kansas State University and the University of Pennsylvania that is informed by the Integrated Clinical Environment (ICE) specification managed by the MD PnP program and its collaborators. The thesis illustrates how to set up the MDCF development environment with Eclipse so that a developer can create software for both a remote MDCF console and a local PCA pump, where ICE channels are used for message transmission. Software development on the MDCF console side includes the development of apps that communicate with a local PCA pump through ICE channels and (b) the development of a GUI that can be launched from an MDCF console to configure, control, and monitor a PCA pump. Software development on the PCA pump side includes the creation of (a) ICE channels that can communicate with an MDCF console and (b) multiple threads for corresponding UART ports that support a modularized design. Several hardware modules were implemented to demonstrate the modularized design approach: an alarm module, a patient button module, a pump module, and a control panel module. These modules employ BeagleBone, Arduino, and MSP430 boards. Status information is displayed on an MDCF console GUI, a PCA pump GUI, and a local LCD screen. An enhanced PCA pump or general medical sub-system with more modules can be developed using a similar method by connecting individual modules to UART ports and then creating the corresponding threads to support device-console communication.
Keywords: PCA Pump; MDCF; ICE Modularized Design; Electrical Engineering (0544)